Neuroplasticity associated with changes in conversational turn-taking following a family-based intervention. (June 2021) - Romeo, Rachel R.; Leonard, Julia A.; Grotzinger, Hannah M.; Robinson, Sydney T.; Takada, Megumi E.; Mackey, Allyson P.; Scherer, Ethan; Rowe, Meredith L.; West, Martin R.; Gabrieli, John D.E.
Highlights: An RCT family-based intervention increased adult-child conversational turns. Across all participants, turn-taking changes (TTC) predicted neurocognitive changes. TTC predicted verbal, nonverbal, and executive functioning improvements. TTC predicted cortical thickening in left inferior frontal and supramarginal regions. Neuroplasticity mediated relationships between TTC and language development. Abstract: Children's early language environments are associated with linguistic, cognitive, and academic development, as well as concurrent brain structure and function. This study investigated neurodevelopmental mechanisms linking language input to development by measuring neuroplasticity associated with an intervention designed to enhance language environments of families primarily from lower socioeconomic backgrounds. Families of 52 4-to-6 year-old children were randomly assigned to a 9-week, interactive, family-based intervention or no-contact control group. Children completed pre- and post-assessments of verbal and nonverbal cognition (n = 52), structural magnetic resonance imaging (n = 45), and home auditory recordings of language exposure (n = 39). Families who completed the intervention exhibited greater increases in adult-child conversational turns, and changes in turn-taking mediated intervention effects on language and executive functioning measures. Collapsing across groups, turn-taking changes were also positively correlated with cortical thickening in left inferior frontal and supramarginal gyri, the latter of which mediated relationships between changes in turn-taking and children's language development. This is the first study of longitudinal neuroplasticity in response to changes in children's language environments, and findings suggest that conversational turns support language development through cortical growth in language and social processing regions. This has implications for early interventions to enhance children's language environments to support neurocognitive development.